Structural, optical and laser damage threshold studies of pure Potassium pentaborate (KB5) crystal - Poornashri Mathangi, R.; Nalini Jayanthi, S.; Shibu, A. (Materials today : proceedings, 2022)
In the current search, the linear and nonlinear optical properties of Potassium Pentaborate (KB5) crystal have been methodically studied. The subject matter of the as grown crystal under single crystal x-ray diffraction analysis recognizes the unit cell parameters and crystal system. On the application of scanning electron microscopic technique, the surface morphology of KB5 crystal has been obtained in a smooth manner. A wider optical transparency is observed using UV–Vis-NIR spectral analysis. The nonlinear optical character of the crystal is tested by Kurtz’s Perry Powder technique. Hence the SHG efficiency of KB5 crystal was observed 2.29 times greater than that of the reference KDP. The positive photoconductivity is attributed with the current analysis. The laser damage threshold testing has proven the ability of the sample for device manufacturing applications. The up gradation of test results in the sample compared with the earlier reported work is a good sign in the study of new electronic materials and devices.